Faktor-faktor yang Memengaruhi Keberdayaan Anggota UPPKS DKI Jakarta menuju Kemandirian Usaha - Sumardji, Lailatur Rohmah; Muljono, Pudji; Purnaningsih, Ninuk; Vitayala, Aida (Jurnal Penyuluhan, 2019)
Poverty is a major and complex problem, various efforts are made to alleviate poverty, but poverty rates do not decrease significantly, due to the low quality of human resources, which causes limited ability to improve welfare. Improving family welfare through UPPKS is a real contribution, and as a driving force for micro businesses in the community. So it needs to be maintained and developed, because it is a place of creativity to be independent and able to work creatively. The study aims to analyze the factors that influence the empowerment of UPPKS members. Data collection was conducted through interviews with 192 UPPKS members. Data analysis in this study included: (1) descriptive analysis in the form of frequency distribution with the help of SPSS and (2) PLS-SEM. The results showed that this hypothesis was tested by comparing tcount values and t-tables for each variable. The t-count value is greater than t-table (1.96) at the 0.05 level. The results of testing the hypothesis indicate that the factors that influence the empowerment of members are the characteristics of members (X1), the empowerment process (X2), the role of members (X3), and the support of the socio-cultural environment (X4). The empowerment of members is more dominantly influenced by the empowerment process (X2) of 0.427. Positive influences indicate that the higher the characteristics of members, the empowerment process, and the support of the socio-cultural environment, the more empowerment will be. Negative influence is that the higher the role of the group, the lower the empowerment of the member. The empowerment of members significantly influences business independence by 0.354, meaning that the higher the empowerment of members, the greater the independence of the business.